2016
DOI: 10.1016/j.imr.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Sasang Personality Questionnaire in high school students

Abstract: BackgroundThe Sasang Personality Questionnaire (SPQ) is an objective measure of Yin–Yang temperament of Sasang typology with proven clinical and structural validity; however, it has not been validated in people younger than 20 years. The purpose of this study was to examine the biopsychological structure of the SPQ in high school students.MethodsA total of 670 Korean high school students (365 boys and 305 girls) completed the SPQ, Junior version of Temperament and Character Inventory (JTCI), and weight and hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…As for the further study, the SPQ for measuring Yin-Yang temperament would need revision for several reasons. The width between the lowest and highest SPQ score of uncertain temperament group was 4-7 in this ( Table 6 ) and previous 7 , 18 , 20 studies, which is relatively small for the clinical use. The variance of SPQ score should be enlarged to provide more precise and detailed cut-off score for Yin-Yang temperament group clustering 14 by adding more questionnaire items not keen to gender and age difference and introducing more than 3 point likert scale with the help of previous biopsychological studies on Yin-Yang temperament and Sasang typology.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…As for the further study, the SPQ for measuring Yin-Yang temperament would need revision for several reasons. The width between the lowest and highest SPQ score of uncertain temperament group was 4-7 in this ( Table 6 ) and previous 7 , 18 , 20 studies, which is relatively small for the clinical use. The variance of SPQ score should be enlarged to provide more precise and detailed cut-off score for Yin-Yang temperament group clustering 14 by adding more questionnaire items not keen to gender and age difference and introducing more than 3 point likert scale with the help of previous biopsychological studies on Yin-Yang temperament and Sasang typology.…”
Section: Discussionmentioning
confidence: 43%
“…The SPQ is a clinical instrument for Yin-Yang temperament with proven validity in adults of 20s-70s, 2 , 9 , 14 high school students, 18 , 19 middle school students 7 , 17 and elementary school students. 20 Though previous studies 9 , 21 have showed acceptable test-retest validity of SPQ with limited number of medical students and others, however, this study provided generalizable stability with large sample sized university students in Busan metropolitan area.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Third, the revision in the current study provided the operational definition of Yin-Yang personality clearly and distinctively by lowering the correlation coefficient among the three rSPQ subscales ( Table 3 ). Previous studies using the SPQ showed significant correlations between SPQ-Behavior and SPQ-Cognition in preschoolers, 28 elementary students, 27 , 28 middle school students, 26 , 36 high school students 12 , 29 and university students, 11 , 13 as well as adults 13 showing correlation coefficient ranged from 0.256 to 0.541. However, the current study showed no significant correlation coefficient between rSPQ-Behavior and rSPQ-Emotion subscales ( Table 3 ), and no significant correlations (r = −0.063∼0.111) among the three rSPQ subscales ( Table 5 ).…”
Section: Discussionmentioning
confidence: 90%
“…Second, adolescents may have difficulty in recognizing and responding to some SPQ items, 26 and gender differences in SPQ-Cognition subscale have also been reported. 12 , 27 , 28 , 29 For example, content of certain questions, such as “Do you consider yourself feminine or masculine?” and “Do you tend to be relatively direct or indirect when expressing yourself”, might have different connotations, depending on the gender, age and cultural background of the individuals. Thus, it requires rectification for easy and correct understandings.…”
Section: Introductionmentioning
confidence: 99%